Sifat-sifat Anti Subgrup Fuzzy - Hira, Cendikia; Abdurrahman, Saman; Thresye, Thresye (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Subgroup is not empty set of group. The group itself is a topic of discussion in abstract algebra which is one of its fundamental parts. In this paper, there further research of group and fuzzy set that produce fuzzy subgroup and anti fuzzy subgroup.